PENDIDIKAN PANCASILA SEBAGAI DASAR NEGARA - Ahmad Arif Fadilah; Muhammad Arivin Ilham; Wildan Ahmad Kholid Nurulfadhil (Sindoro: Cendikia Pendidikan, 2025)
In This Article, We Will See How Pancasila Functions As A Legal Basis For National Life. Every Aspect Of Indonesian Law Enforcement Is Based On Pancasila. The Purpose Of This Journal Is To Improve Public Understanding Of What Pancasila Is, Its Functions, And Position, As Well As The Principles Contained In Its Principles, And How These Principles Can Be Applied In Daily Life And Also To Improve Understanding And Comprehension Of Pancasila As The Basis Of The State. The Author Is Interested In Analyzing The Topic Of Pancasila As The Basis Of The State Because It Is Very Important To Develop Very Important Knowledge For The Nation.